Aggregation‐Induced Emission‐Based Platforms for the Treatment of Bacteria, Fungi, and Viruses. Issue 24 (30th June 2021) - Chen, Xiaohui; Han, Haijie; Tang, Zhe; Jin, Qiao; Ji, Jian
Abstract: The prevention and control of pathogenic bacteria, fungi, and viruses is a herculean task for all the countries since they greatly threaten global public health. Rapid detection and effective elimination of these pathogens is crucial for the treatment of related diseases. It is urgently demanded to develop new diagnostic and therapeutic strategies to combat bacteria, fungi, and viruses‐induced infections. The emergence of aggregation‐induced emission (AIE) luminogens (AIEgens) is a revolutionary breakthrough for the treatment of many diseases, including pathogenic infections. In this review, the main focus is on the applications of AIEgens for theranostic treatment of pathogenic bacteria, fungi, and viruses. Due to the AIE characteristic, AIEgens are promising fluorescent probes for the detection of bacteria, fungi, and viruses with excellent sensitivity and photostability. Moreover, AIEgen‐based theranostic platforms can be fabricated by introducing bactericidal moieties or designing AIE photosensitizers and AIE photothermal agents. The current strategies and ongoing developments of AIEgens for the treatment of pathogenic bacteria, fungi, and viruses will be discussed in detail. Abstract : The current strategies of aggregation‐induced emission (AIE) luminogens (AIEgens) for the theranostic treatment of pathogenic bacteria, fungi, and viruses are summarized in this review. AIEgens are promising fluorescent probes for the detection of bacteria, fungi, and viruses due to its excellent sensitivity and photostability. Moreover, AIEgen‐based theranostic platforms can be fabricated by introducing bactericidal moieties or designing AIE photosensitizers and AIE photothermal agents.